Surrogacy in Portugal: Guidelines for clinical practice - Pinheiro, Sofia; Ricou, Miguel; Pereira, Helena (Acta Bioethica, 2024)
Introduction: The approval by the Portuguese Parliament, in December 2021, of the law applicable to Surrogate Pregnancy, raises reflection on the practical aspects in which the scheme will be implemented and the necessary guidelines for health professionals involved. For this reason, the following objectives were defined: to analyze a set of recommendations for clinical practice in surrogacy in countries with experience in the procedure and to promote a discussion with experts in Medically Assisted Reproduction. Material and Methods: A documental analysis of publications and official documents on the theme was conducted. This served as a basis for the qualitative design study based on focus groups with different professionals —physicians, and psychologists— with experience in Medically Assisted Reproduction. The discussion was realized through sessions via Zoom®, held separately with the two focus groups. Results: In the debate, the experts made their appreciation and proposals for improvement concerning the initial version of the document resulting from the document analysis. Conclusion: A consolidated version of the set of guidelines for health professionals was obtained with the dimensions to evaluate and follow up with the surrogate and beneficiaries in Surrogacy.